Analysis of Information Technology Governance in the SaData-Ku Application at the Kuningan Regency Regional Development Planning, Research and Development Agency (BAPPEDA) Using the COBIT 2019 Framework - Pratama, Eneng Kurnia Dewi; Gufroni, Acep Irham (Deparment Information System, Siliwangi University, 2024)
Currently, the success and continuity of a company or organization is very much based on IT, in terms of speed and results that can help increase the effectiveness and efficiency of business processes to achieve goals. In its implementation, the Regional Development Planning, Research and Development Agency (BAPPEDA) of Kuningan Regency encountered problems with the SaData-Ku application, errors occurred when inputting data (system failure to operate), there was a risk that when collecting data there was a delay from the predetermined schedule, the operation of the application was limited in time. for data input, resulting in bugs in the application. This problem has a negative impact on the continuity of the development planning process and can reduce the quality performance of information technology. To overcome this, application users need learning and growth to become more proficient in the field of information technology, thereby reducing difficulties in dealing with sudden changes or disruptions to applications. These problems can be identified thoroughly with governance using the COBIT 2019 framework. The form and content of the COBIT 2019 model are updated from the previous COBIT method and many new functions are added, including enabling improvements to the IT governance system. By conducting analysis, you can provide recommendations to improve the organization's capabilities to meet the agency's expectations and goals regarding IT governance in supporting its performance. The COBIT 2019 domains used are APO and DSS with details of the APO07, APO12, APO14 and DSS01 processes. The results of measuring the capability level of the APO07 domain at the Kuningan Regency Regional Development Planning, Research and Development Agency (BAPPEDA) got a capability level 4 value, the APO12, APO14 and DSS01 domains got a capability level 5 value.